Discursive representations of domestic helpers in cyberspace. (February 2020) - Ho, Janet
This study investigates the online narratives Hong Kong employers construct around foreign domestic helpers (FDHs) and aims to compensate for the existing gap in discursive research and mainstream media, which tend to focus on the perspective of FDHs. It examines how employers portrayed FDHs both positively and negatively, as well as how they represented themselves in online environments. Critical discourse analysis was used to analyse more than 2000 Facebook posts on the subject of FDHs, identifying discursive strategies used in constructing both power dynamics and identities. The findings revealed that nomination strategies dominated the discourse, constructing both the in- and out-group identities of FDHs. Other strategies, such as predication and augmentation, showed how employers portrayed themselves as opportunity-givers and food critics, which further contributed to the inferior self-perception of FDHs. The study concludes that employers have developed a sense of ideological ambivalence, in which they perceived FDHs as motherly figures while simultaneously maintaining their superior status.